2022
DOI: 10.1088/1361-648x/ac4347
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, phonons and optical properties of baryte type scintillators TlXO4 (X = Cl, Br)

Abstract: This article thoroughly addresses the structural, mechanical, vibrational, electronic band structure and the optical properties of the unexplored thallous perchlorate and perbromate from ab-initio calculations. The zone centered vibrational phonon frequencies shows, there is a blue shift in the mid and high frequency range from Cl → Br due to change in mass and force constant with respect to oxygen atom. From the band structure it is clear that the top of the valence band is due to thallium s states, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The energy difference between the two structures is however small (Table S1). Both structures are insulators with large band gaps (Figures S24 and S25 and Table S1), where the Tl 6s 2 electrons play a major role in the valence band region . The transition between the monoclinic and tetragonal structures in TlReO 4 strongly impacts the anion sublattice, as shown by the significant differences in the arrangement of the ReO 4 tetrahedra (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…The energy difference between the two structures is however small (Table S1). Both structures are insulators with large band gaps (Figures S24 and S25 and Table S1), where the Tl 6s 2 electrons play a major role in the valence band region . The transition between the monoclinic and tetragonal structures in TlReO 4 strongly impacts the anion sublattice, as shown by the significant differences in the arrangement of the ReO 4 tetrahedra (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…17−19 Furthermore, recent investigations suggest potential applications for thallous perchlorate and perbromate as inorganic scintillators, indicating the intricate charge-transfer dynamics within these materials. 20 Studies on TlReO 4 have highlighted the significant influence of Tl + 6s 2 lone pair electrons on determining its electronic and structural properties, suggesting the possibility of tuning the energy landscape of ABO 4 compounds containing lone pair electrons through chemical doping. 21,22 Notably, the arsenates, chromates, vanadates, silicates, and phosphates tend to crystallize in zircon-type structures, although certain arsenates and phosphates deviate from these structures, adopting quartz structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These oxides appear in different structural forms, such as scheelite, pseudoscheelite, zircon, fergusonite, barite, monazite, and wolframite. Such structural flexibility leads to temperature or pressure-induced phase transitions; for example, with increasing temperature, transformations from monazite to scheelite to zircon can occur, while under increasing pressure, the reverse sequence unfolds, transitioning from zircon to monazite to scheelite . The diverse nature of ABO 4 -type compounds is further emphasized by their wide-ranging applications, which include phosphors such as ZrGeO 4 and HfGeO 4 ; battery materials such as CaMoO 4 and SrWO 4 ; laser host materials such as BaWO 4 and GdTaO 4 ; , and scintillators such as CdWO 4 and PbWO 4 . , Intriguingly, high-pressure studies have highlighted major differences, with orthovanadates exhibiting superior scintillating properties compared to those of periodates. Furthermore, recent investigations suggest potential applications for thallous perchlorate and perbromate as inorganic scintillators, indicating the intricate charge-transfer dynamics within these materials …”
Section: Introductionmentioning
confidence: 99%
“…[ 6–8 ] Our recent study suggests that thallous perchlorate and perbromate can be used as inorganic scintillators, since there exists a charge‐transfer character in the bands. [ 9 ] It is generally found that the structure of the ABO4 oxides favored under ambient conditions is dependent on the smaller, more highly charged, B‐type cation. Phosphates, silicates, vanadates, chromates, and arsenates are known to crystallize in the zircon‐type structure, although several phosphates and arsenates crystallize in the quartz structure, whereas the scheelite structure is observed for numerous molybdates, tungstates, iodates, and germanates.…”
Section: Introductionmentioning
confidence: 99%